2021
DOI: 10.3389/fgene.2021.627974
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Genes Associated With Sexual Dichromatism of Head Feather Color in Mallard

Abstract: Sexual dimorphism of feather color is typical in mallards, in which drakes exhibit green head feathers, while females show dull head feather color. We showed that more melanosomes deposited in the males’ head’s feather barbules than females and further form a two-dimensional hexagonal lattice, which conferred the green feather coloration of drakes. Additionally, transcriptome analysis revealed that some essential melanin biosynthesis genes were highly expressed in feather follicles during the development of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
4
9
0
Order By: Relevance
“…This supports the concept of sex-based differences in melanin levels on the dorsal skin of Hungarian white geese. Furthermore, similar sexual dimorphism has been observed in Barn Swallows [6] and mallards [23], it has been attributed to signi cant sex-speci c variations in determinants in uencing melanin deposition and feather coloration. Based on our ndings and previous research, it becomes evident that the coloration of the dorsal down in newborn Hungarian white geese exhibits sexual dimorphism, closely associated with both the quantity and distribution of melanin within the feather follicle.…”
Section: Discussionsupporting
confidence: 53%
“…This supports the concept of sex-based differences in melanin levels on the dorsal skin of Hungarian white geese. Furthermore, similar sexual dimorphism has been observed in Barn Swallows [6] and mallards [23], it has been attributed to signi cant sex-speci c variations in determinants in uencing melanin deposition and feather coloration. Based on our ndings and previous research, it becomes evident that the coloration of the dorsal down in newborn Hungarian white geese exhibits sexual dimorphism, closely associated with both the quantity and distribution of melanin within the feather follicle.…”
Section: Discussionsupporting
confidence: 53%
“…Further functional enrichment analysis indicated that CACNA1I , WDR59 , GNAO1 and CACNA2D4 genes might be critical for green heads formation of male ducks. These genes are mainly involved in the MAPK signaling pathway, melanogenesis, mTOR signaling pathway and calcium signaling pathway, which are closely related to the regulation of melanin synthesis and metabolism (Li et al, 2018; Ma et al, 2021; Park et al, 2015; Qi et al, 2022; Wang, Xi, et al, 2022b). Therefore, we considered that mutations in genes related to melanin synthesis and metabolism pathways would affect melanin synthesis and subsequently affect individual green head trait differences in male ducks.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that phenotypic diversity is abundant in this study population. Moreover, previous studies have shown that the content of eumelanin plays a dominant role in forming the green head of male ducks (Eliason & Shawkey, 2012;Haase et al, 1995;Khudiyev et al, 2014;Ma et al, 2021). However, melanin synthesis is environmentally and genetically co-controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the head feathers of male wild ducks appeared green, whereas females exhibited a subdued head feather color. Genes such as TYR, SLC38A11, REELD1, and SYNPR may influence the distinct color differences between the head and back feathers of males and the head feathers of females, with TYR and TYRP1 being directly related to melanin biosynthesis [15]. Knobs represent a unique appearance characteristic of geese, but their tissue morphology and genetic mechanisms have not yet been revealed.…”
Section: Introductionmentioning
confidence: 99%